Assessing Treatment Integrity in Alcohol Behavioral Couple Therapy. (June 2016) - Hallgren, Kevin A.; Crotwell, Shirley M.; Muñoz, Rosa E.; Gius, Becky K.; McCrady, Barbara S.; Ladd, Benjamin O.; Epstein, Elizabeth E.
Abstract : Objectives: Alcohol Behavioral Couple Therapy (ABCT) is an efficacious treatment for alcohol-use disorders. Coding treatment integrity can shed light on the active ingredients of ABCT, but there are no published studies of treatment integrity instruments for ABCT. The present study describes the development and initial reliability of the Treatment Integrity Rating System-Couples Version (C-TIRS) for ABCT. Materials and Methods: The C-TIRS was used to rate 284 first and mid-treatment ABCT sessions of 188 couples in 4 randomized clinical trials. Results: Average interrater reliability for distinguishing ratings between C-TIRS items was fair to good for quantity items [intraclass correlation (ICC)=0.64] and poor to fair for quality items (ICC=0.41). Five C-TIRS subscales were defined a priori to measure treatment components involving cognitive-behavioral therapy, spouse involvement, couple therapy, common therapeutic factors, and overall adherence to the treatment protocol and had adequate internal reliability (α=0.74 to 0.89). Interrater reliability was fair to good on 7 of 10 scales, but poor on 3 scales (ICC range=0.17 to 0.72). Conclusions: The C-TIRS was designed to provide information about quantity and quality of the delivery of ABCT components; however, further refinement of the C-TIRS is warranted before it should be used in frontline practice. Clinical implications and recommendations for future research are discussed. Abstract : Supplemental Digital Content is available in the text.